(untitled) (Proceedings of International Educators Conference, 2023)
Properly raise children, it is necessary to know the main characteristics of their body, such as growth and development. Growth and development is a characteristic of the human body, like all living organisms. All-round growth and development of the organism begins from the moment of its appearance. These two processes are considered complex, integrated and interconnected .